Composition, distribution and abundance of macrobenthos in the mangrove areas in Tagana-an, Surigao Del Norte. - Depita, Ayra C
The macroinfau7na was sampled in mangrove and outside mangrove areas in Tagana-an, Sirogao del Norte, Philippines on May 4, 2017 with the purpose of determining the spatial distribution, abundance and composition of macroinfaunal densities inside and outside the mangrove areas. A total of 24 macroinfaunanal taxa was identified with a total mean density of 770.20 ind.m-2 found to be comparable with other mangrove and seagrass habitats in and outside the Philippines. Of the identifies macrofaunal taxa, the polychaetes (64%) were the most abundant, followed by crustaceans (28%) and mollusks (6%). Among the polychaete group, species belonging to families Paraonidae (16%), Syllidae (12%) and Spionidae (11%) dominated all mangrove stations, inside and outside the mangrove area. Polychaetes are opportunistic organisms; they have varying feeding behaviors, reproductive strategies which allow them to thrive even in areas hostile to other species and continue to proliferate even under extreme conditions. Statistical analysis showed no significant difference on macrofaunal densities across all stations (F=0.52, p+0.73, Fcrit=5.19), which proved that the locations of the stations, whether they were located outside or indside the mangrove area, did not considerably contribute to the variation in mean macrofaunal densities. Burrowers and deposit feeders like polychaetes were most abundant in medium sand sediments which suggests that polychaetes prefer for finer sediments positively correlated with higher cohesivity of organic matter, which serve as food for these organisms. Mollusks and crustaceans, on the other hand, prefer coarse sediments as they need interstitial spaces for their mobility. Overall, the macrofauna showed weak positive correlation with sediment characteristics, higher % sand sediment (R=0.138), specifically to granules (R=0.79), very coarse sand (R=0.435) and coarse sand (R=0.1083), suggesting that sediment characteristic is not the main factor affecting macrofaunal distribution and abundance in Tagana-an, Surigao del Norte mangrove areas but may also be linked to biotic (feeding behaviors, competition and predation) and abiotic factors (salinity, pH, temperature, anthropogenic activites).